Physical performance among community-dwelling older people in Senawang - Ibrahim, Amirah Fatin; Teoh, Gaik Kin; Chong, Mei Chan; Tan, Maw Pin; Muda, Siti Mariam; Khoo, Phaik Lin (Oxford University Press, 2019)
Introduction Older adults may remove themselves voluntarily from social activities due to health concerns and physical limitations that leads to loneliness. Additionally, loneliness is associated with poorer health among older adults. Therefore, this study aims to improve health status among community-dwelling older adults in the sub-urban area through this social participation project by creating awareness on empowering the older adults in managing their health and social life.